Is the Nature (Extent and Characteristics) of Schistosoma-Induced Chronic Inflammation Organ Dependents? - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Pathogenesis of schistosomiasis related bladder cancer has been attributed to induced chronic inflammation and its sequelae. There is paucity of studies on the inflammatory cell profile.Aim:This study, therefore, aims to characterise the degree and repertoire of this inflammatory response.Settings and Design:A retrospective study of all non-neoplastic cases of schistosomiasis histologically confirmed between January 2012 and December 2019 in a tertiary hospital.Materials and Methods:Data were retrieved from archives and slides made for the cases were evaluated for ova density, type and degree of inflammation and pattern of fibrosis.Statistical Analysis:The degree of inter observer variation (kappa value) was also calculated while statistical significance was set at P ≤ 0.5 at 95% confidence interval.Results:Eighty one cases were diagnosed in the study period. The mean age was 33.8 years and M:F ratio was 15:1. Bladder, ureter, gastrointestinal tract, testes and other less frequent sites accounted for 58.0%, 12.0%, 8.0%, 8.0% and 7.4% of cases, respectively. Eosinophilic infiltration and granulomatous reaction were predominantly minimal even in cases with significant oviposition. There was no significant difference between ova density and degree of overall inflammation (P= 0.9) or between ova density and degree of lymphocytic infiltration (P= 0.2). Similarly, even though fibrosis was more frequent in cases with high ova density, no significant difference was found in cases with low ova density.Conclusion:Even though carcinogenesis in bladder schistosomiasis has been attributed to chronic inflammation and fibrosis, this study, however, showed that there are no statistically significant differences between schistosoma ova density and degree of inflammation as well as fibrosis in both bladder and other organs.